Associação entre polimorfismos do gene do receptor alfa de estrogênio com a densidade mamográfica em mulheres após a menopausa - Ramos, Eduardo Henrique de Moura [UNIFESP] (2009)
Introduction: Genes that encode proteins involved at biosynthesis, action and metabolism of sexual steroids are polymorphics. This condition could explain individual variations in mammographic density. The objectives of this study were to evaluate a possible association of clinical characteristics and polymorphisms HaeIII, MspI and XbaI of the estrogen receptor gene alpha with postmenopausal mammographic density. Methods: Prospective evaluation was made of 120 women who were not hormone therapy users and had no identified breast lesions. Bilateral mammography was obtained from the group, and the radiological density was determined by three independent observers, with two subjective evaluations based on the ACR-BIRADS® (2003) classification of mammographic patterns and one computerized evaluation – the grey-scale histogram tool of the Adobe Photoshop® 7.0 software. Peripheral blood samples were obtained for DNA extraction, performed according to the GFX® Kit protocol from Amersham-Pharmacia. PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphism) was carried out for an analysis of the polymorphisms present in intron 1 (HaeIII and XbaI) and in exon 1 (MspI) of the estrogen receptor gene. Results: There was a high degree of concordance among the observers in the determination of mammographic density (Kappa, Pearson and Spearman index - p<0.001). The associations of clinical characteristics with mammographic density were: age (p=0,04), body mass index (p<0.0001), age at menarche (p=0.02), age at menopause (p=0.120), age at first delivery (p=0.120) and parity (p=0.09). The relation between the allele distribution of the polymorphisms and the density was: XbaI (p=0.02), HaeIII (p=0.65) and MspI (p=0.65). Conclusion: Polymorphism XbaI and the clinical factors age, menarche and body mass index showed to be associated with postmenopausal mammographic density.